Selected Papers from the 11th Asian Rock Mechanics Symposium (ARMS 11) - Zhu, Chun; Tao, Zhigang; Yang, Xiaojie; Sun, Jianping (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The problem of rock mechanics and engineering is an old and new subject encountered by human beings in their struggle with nature for survival and development. To call it ancient means that it has a long history; however, speaking of it as brand-new refers to the continuous emergence of new problems and new situations in engineering practice, which is quite challenging. With the development of human engineering activities, the issues surrounding rock engineering are becoming more and more prominent, and the problems encountered are becoming more and more complex. In the practice of solving complex rock engineering, human beings have summarized many topics that are difficult to explain or solve with classical mechanics.